Integration of Video Games in Teaching and Learning at School: Use, Analyze, Make-create - Ivanauskienė, Gintė Marija (Vilnius University Open Series, 2020)
This article aims to reveal different ways of integrating video games, and emerging challenges in Lithuanian schools. The integration of computer games is exposed by selecting the project Big Small Screens. Media Literacy in Schools of Lithuania and analyzing the experience of teachers who participated in this project. The research showed that the project activities invite teachers and pupils to change the perspective of their view and become critics or creators. However, while the integration of video games can bring many positive results, this process also contains a number of challenges. Therefore, after the end of the project, the possibilities for further integration of video games into formal education remain limited.